2022
DOI: 10.1155/2022/8016567
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Nursing Intervention Based on Intelligent Grip Strength System in Patients with Tumor PICC: A Case-Control Study on Promoting Functional Exercise and Quality of Life

Abstract: Objective. A case-control study was conducted to elucidate the impact of application of nursing intervention based on intelligent grip strength system in patients with tumor peripherally inserted central catheter (PICC) on promoting functional exercise and life quality. Methods. A total of 100 patients with tumor PICC treated in our hospital from April 2019 to April 2021 were enrolled. The patients were randomly assigned into control group and study group. The control group received routine nursing, and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For breast cancer patients who have just undergone surgery [ 23 ], they are psychologically vulnerable, both from having a physical disability after surgery [ 24 ] and from the fear of about to start chemotherapy [ 25 ]. It has been shown that the majority of patients have anxiety after PICC placement [ 26 ], and in this study, it was found that the change in anxiety and depression scores in the control group after PICC placement in breast cancer patients generally increased by 2-3 points compared to the test group. The reasons for this may be due to the lack of knowledge about PICC placement and the restriction of limb movement on the side of the placement, which put the patients in a state of tension and anxiety, and the leakage of blood from the puncture port after placement, which further increased the depression and anxiety of the patients.…”
Section: Discussionmentioning
confidence: 54%
“…For breast cancer patients who have just undergone surgery [ 23 ], they are psychologically vulnerable, both from having a physical disability after surgery [ 24 ] and from the fear of about to start chemotherapy [ 25 ]. It has been shown that the majority of patients have anxiety after PICC placement [ 26 ], and in this study, it was found that the change in anxiety and depression scores in the control group after PICC placement in breast cancer patients generally increased by 2-3 points compared to the test group. The reasons for this may be due to the lack of knowledge about PICC placement and the restriction of limb movement on the side of the placement, which put the patients in a state of tension and anxiety, and the leakage of blood from the puncture port after placement, which further increased the depression and anxiety of the patients.…”
Section: Discussionmentioning
confidence: 54%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%